The effect of favipiravir on fracture healing - Mehmet Ali Sabır; Ahmet Onur Çelik; Elif Mercan Demirtaş; Cem Çopuroğlu (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: The aim of this study was to evaluate the effects of favipiravir on fracture healing.